Comparative Analysis of Building Structure Work Cost Estimation with BIM Construction Approach Case Study: Construction Project of Main Lecture Building of P4T Flagship Program of Empat Lawang Regency - Pramana, I Putu Leo; Susanti, Betty; Adhitya, Bimo Brata (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Volume estimation and Bill of Quantities (BOQ) are crucial processes in construction planning. Currently, volume and BOQ calculations are still done manually by calculating the volume of each component in the working drawings. This process is time-consuming and prone to human error. One way to improve efficiency is to implement Building Information Modeling (BIM) in volume estimation and BOQ calculation to enhance work effectiveness. Autodesk Revit is one software that can assist in 3D modeling and accurate volume calculation. This research discusses how BIM can aid in the design volume calculation process and BOQ planning for the Main Lecture Hall building within the Integrated Agricultural Research and Development Center (P4T). Compared to conventional methods, the results show that implementing BIM on this project has provided significant benefits in terms of efficiency, increased calculation accuracy, material usage, and cost savings. With an optimization of concrete material usage by approximately 1,35% and reinforcement volume by approximately 2.11%, and a cost reduction of 0,985%, BIM has proven to provide significant added value to the project.